2010
DOI: 10.1074/jbc.m110.102459
|View full text |Cite
|
Sign up to set email alerts
|

Hantavirus Nucleocapsid Protein Has Distinct m7G Cap- and RNA-binding Sites

Abstract: Hantaviruses, members of the Bunyaviridae family, are emerging category A pathogens that carry three negative stranded RNA molecules as their genome. Hantavirus nucleocapsid protein (N) is encoded by the smallest S segment genomic RNA (viral RNA). N specifically binds mRNA caps and requires four nucleotides adjacent to the cap for high affinity binding. We show that the N peptide has distinct cap-and RNA-binding sites that independently interact with mRNA cap and viral genomic RNA, respectively. In addition, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 61 publications
4
60
0
Order By: Relevance
“…One interesting example of a viral protein interacting with host ribosomal proteins is the case of the hantavirus nucleocapsid (N) protein, which interacts with the RPS19 protein (47)(48)(49). It has been shown that RPS19 interaction with N protein facilitates ribosome loading onto the viral RNA transcripts, leading to preferential translation of viral transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…One interesting example of a viral protein interacting with host ribosomal proteins is the case of the hantavirus nucleocapsid (N) protein, which interacts with the RPS19 protein (47)(48)(49). It has been shown that RPS19 interaction with N protein facilitates ribosome loading onto the viral RNA transcripts, leading to preferential translation of viral transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…We also used continuous variation plots to verify the binding stoichiometry results as reported previously (14,59,60). This is a reliable method to determine the binding stoichiometry of protein-protein complexes.…”
Section: Methodsmentioning
confidence: 99%
“…Calculation of Binding Stoichiometry-As described previously (14,59), the binding stoichiometry (expressed in terms of the number of RPS19 molecules bound per molecule of N) was estimated from the intersection of two straight lines of a least square fit plot of ⌬F/⌬F max against the ratio of input concentrations of N and 1,5-IAEDANS-labeled RPS19. We also used continuous variation plots to verify the binding stoichiometry results as reported previously (14,59,60).…”
Section: Methodsmentioning
confidence: 99%
“…Rather, all segmented negative-sense RNA viruses (bunyaviruses, arenaviruses, and orthomyxoviruses) ''cap-snatch'' the 59 ends of host mRNAs, simultaneously defending the 59 end of their mRNAs from exonucleases and facilitating translation. Bunyavirus-encoded N protein specifically binds the 59 caps of host mRNAs (Mir et al 2010). The viral RNAdependent RNA polymerase (L), which has endonucleolytic activity (Patterson et al 1984;Reguera et al 2010), then cleaves host mRNAs 10-18 nucleotides (nt) downstream from the 59 cap and uses this primer as a template for viral mRNA transcription (Patterson et al 1984;Bouloy et al 1990;Simons and Pettersson 1991).…”
Section: Dcp2 Does Not Restrict Rvfv By Directly Decapping Viral Mrnasmentioning
confidence: 99%
“…Of these, influenza A virus, an orthomyxovirus, is the best studied and snatches the 59 end of pre-mRNAs in the nucleus (Herz et al 1981;Plotch et al 1981). Since bunyaviruses and arenaviruses replicate in the cytoplasm, they must use a distinct pool of mRNAs; however, while our mechanistic understanding of bunyaviral cap-snatching is increasing (van Poelwijk et al 1996;van Knippenberg et al 2005;Mir et al 2010;Morin et al 2010;Reguera et al 2010;Cheng and Mir 2012), little is known about whether the host can combat this replication step or what pool of endogenous mRNAs are being targeted for this process.…”
mentioning
confidence: 99%